Konsep Penataan Ruang Kawasan Rawan Bencana (KRB) Tsunami di Kabupaten Karangasem, Pulau Bali: Spatial Planning Concept of Tsunami Disaster Prone Area in Karangasem Regency, Bali Island - Rizki Kirana Yuniartanti (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2021)
The island of Bali and its surrounding are part of Indonesia's seism tectonic system. The condition has been faced including by Karangasem Regency. Karangasem Regency is prone by seismic and tsunami disaster. The high level of disaster proneness in Karangasem Regency requires disaster preparedness in pre-disaster phase. Rehabilitation and reconstruction responses are not been effective since these steps require expensive funding and investment. Preparedness efforts in pre-disaster phase are carried out through quality enhancement of spatial plans based on Disaster Risk Reduction (DRR). This research is aimed to provide recommendation for spatial plan, including spatial pattern (land use) plan and development of mitigation infrastructure. This research uses qualitative and quantitative research methods. Analysis tools are Geographic Information Systems (GIS), good practices, and literatures, as well as policies from various sources. The output of this study resulted in a spatial assessment according to the level of tsunami disaster prone level.